BIBLIOGRAPHIC RESEARCH ON SCIENTIFIC STUDIES RELATED TO BITCOIN AND BLOCKCHAIN - Castañeda-Ayarza, Juan Arturo; Neves, Cíntia; Frazão Teixeira, André (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
Digital currencies represent a new technological and monetary dynamics in the development of information technologies and internet. Bitcoin, a virtual currency that emerged in 2008 as a computer code, is characterized by being free of ties to monetary authorities and by not having nationality. The growing interest in Bitcoin is also found in science. Thus, our objective was to map the scientific knowledge about Bitcoin and Blockchain technology. Through bibliographic research in two databases, Science Direct and Scielo, 432 publications were mapped between 2008 and 2018. Out of these, 80% happened between 2016 and 2018, highlighting the rapid growth of scientific production. The main research topics are related to the Bitcoin market, the safety and efficiency of Blockchain technology, the illegal market, as well as the potential applications in areas such as energy, health, shared economy, Big Data and Internet of Things.